Obesity increases the risk of small intestinal bacterial overgrowth (SIBO) - Roland, B. C.; Lee, D.; Miller, L. S.; Vegesna, A.; Yolken, R.; Severance, E.; Prandovszky, E.; Zheng, X. E.; Mullin, G. E. (Neurogastroenterology and motility, 2018)
Background Small intestinal bacterial overgrowth (SIBO) has been associated with anatomical and motility‐related abnormalities. Specifically, obesity has been postulated to alter small bowel motility, leading to SIBO. Aims (i) Assess the prevalence of SIBO in obesity; (ii) determine the relationship of obesity and SIBO, using small bowel transit time (SBTT) and pH; (iii) profile the gut microbiome in obese and non‐obese patients with SIBO. Methods Thirty consecutive participants referred for SIBO underwent lactulose breath tests (LBTs) and wireless motility capsule (WMC) studies. Composition of the intestinal microbiome was assessed by analyzing samples from three different gastrointestinal sites via 16S rRNA gene‐sequencing. Key Results SIBO was more frequent among obese patients vs non‐obese patients (88.9% vs 42.9%, P < .05). Obesity did not correlate with small bowel transit time (SBTT), gastric pH, and small bowel pH. In patients with normal SBTT, obesity was associated with an 11‐fold increase (P = .05) in the risk of SIBO. Whereas in those with prolonged SBTT, there was no correlation between obesity and SIBO. Obese vs non‐obese patients exhibited significant differences in microbiome diversity in rectal samples. Obesity was associated with increased odds of developing SIBO (P = .04) in multivariate regression analyses. Conclusions and Inferences While obesity was significantly associated with SIBO, our findings suggest that alterations in gut pH, SBTT, and decline in species richness do not account for the obesity–SIBO relationship. Patients undergoing breath hydrogen and methane testing at a tertiary care outpatient center were found to have a higher risk of having small intestine bacterial overgrowth (SIBO) when compared with non‐obese control subjects. The chronic use of proton pump inhibitors was not found to contribute to this observation.